2011
DOI: 10.5005/jp-journals-10024-1031
|View full text |Cite
|
Sign up to set email alerts
|

Retention Strength of Cobalt-Chromium vs Nickel-Chromium Titanium vs CP Titanium in a Cast Framework Association of Removable Partial Overdenture

Abstract: Aim: There is little information considering the framework association between cast clasps and attachments. The aim of this study was to evaluate the retention strength of frameworks match circumferential clasps and extra resilient attachment cast in three different alloys (cobalt-chromium, nickel-chromium titanium and commercially pure titanium), using two undercut (0.25 and 0.75 mm) and considering different period of time (0, 1/2, 1, 2, 3, 4 and 5 years). Methods:Using two metallic matrices, representing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…However, the durability of titanium and Ti-6Al-4V clasps has been questioned 39) . Some methods used to measure the retentive forces have indicated that the retentive force of titanium clasps is about half of that of cobalt alloys 40,41) .…”
Section: Application Of Titanium and Its Alloys For Removable Dental ...mentioning
confidence: 99%
“…However, the durability of titanium and Ti-6Al-4V clasps has been questioned 39) . Some methods used to measure the retentive forces have indicated that the retentive force of titanium clasps is about half of that of cobalt alloys 40,41) .…”
Section: Application Of Titanium and Its Alloys For Removable Dental ...mentioning
confidence: 99%
“…The CAD software (3Shape Dental System, version 2.9.9.3) was then used to design the Aker clasp and generate a standard triangulation language (STL file) then transferred to a computer aided machine (CAM) (Redon milling machine) to mild Aker clasp from Ni/Ti alloy and PEEK blocks. [16]…”
Section: Fabrication Of Cad/cam Milledpeek and Ni/ Ti Claspsmentioning
confidence: 99%